The Auckland keratoconus study: Identifying predictors of acute corneal hydrops in keratoconus. (21st February 2013) - Fan Gaskin, Jennifer C; Good, William R; Jordan, Charlotte A; Patel, Dipika V; McGhee, Charles NJ
<x xml:space="preserve">Abstract</x> Background The aim was to identify potential factors associated with acute corneal hydrops in a New Zealand population with keratoconus referred to a hospital eye service. Methods In a single hospital centre, in a retrospective review, demographic and clinical features of subjects with keratoconus and corneal hydrops over a 17‐year period were compared with an age‐ and gender‐matched control group of subjects with keratoconus but no history of corneal hydrops. Results One hundred and one eyes of 101 subjects (mean age 24.6 ± 8.4 years) were identified with keratoconus‐related corneal hydrops. Subjects were more likely to be of Pacific but less likely to be of New Zealand European ethnicity than control subjects (n = 101). In comparison, Maori ethnicity was not found to have a significantly positive or negative association with hydrops. The pre‐hydrops visual acuity (VA) of affected eyes was poorer than that of controls (p < 0.001) at first presentation to our tertiary referral corneal and contact lens service. Hydrops typically developed approximately four years after diagnosis of keratoconus. Subjects with hydrops were more likely to have a history of eye‐rubbing (p = 0.011) but less likely to have a family history of keratoconus (p = 0.05). In 31 cases, the acute hydrops event was their first optometric/ophthalmologic contact. There were no statistically significant differences in the prevalence of atopic disease, contact lens wear or overall corneal transplantation rate between the two groups. Conclusions Pacific ethnicity, history of eye‐rubbing, poor VA at first hospital presentation and lack of family history were statistically associated with developing acute corneal hydrops in keratoconus in a New Zealand population. Greater understanding of such predisposing risk factors may help develop early management strategies to delay or prevent progression of this disease.